Points de repère - Coulomb, Pierre; Delorme, Hélène (Études internationales, 1981)
The production and consumption of food occupy a major share of the general concern brought about by the world crisis. The growth of both elements continues nevertheless in keeping with the same capital-intensive and labour-saving standards of the previous expansionary phase. But the new context of world inflation, instability and recession imposes a burden with regard to the reproduction costs of food Systems in all of the OECD countries. Indeed, three trends are evolving simultaneously : the increase in the price of land; the instability of domestic price Systems; and, the new influence of international markets.